Position vector of spacelike biharmonic slant helices with timelike principal normal according to Bishop frame in Minkowski 3-space - Turhan, Essin; Korpinar, Talat (Academic Journals, 2010)
In this paper, we study spacelike biharmonic curves with timelike principal normal according to Bishop frame in Minkowski 3-space E-1(3) and give some characterizations for curvature and torsion of a biharmonic curve in Minkowski 3-space E-1(3).. Moreover, the position vectors of spacelike biharmonic slant helices were obtained in Minkowski 3-space E-1(3).
Keywords: Energy; bienergy; biharmonic curve; Minkowski 3-space